Pengaruh Kombinasi Pijat Oksitosin, Pijat Laktasi dan Akupresur Terhadap Produksi Asi Ibu Postpartum 0-3 Hari - Ezzy Gapmelezy; Mutia Dewi Meilawati; Ita Herawati; Titi Amalia (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
According to (Jakarta Provincial Health Office, 2023) the coverage of exclusive breastfeeding in DKI Jakarta province in 2022 was 50.11% and the coverage rate of exclusive breastfeeding in South Jakarta in 2022 was 50.32%, although the coverage is large, there are quite a lot of mothers who have not given exclusive breastfeeding to their children. One of the factors that causes the failure of the implementation of exclusive breastfeeding is because in the first 3 days or in the early period after delivery, breast milk has not come out so that it becomes a reason for mothers and families to give formula milk (Aprilianti, 2019). This study aims to determine the effect of a combination of oxytocin massage, lactation massage and acupressure on breast milk production in postpartum mothers aged 0-3 days at TPMB Yevi Yesevi, AMd. Keb South Jakarta in 2023. The benefits of this study can provide knowledge and insight to the community in performing massage related to breast milk production. This study uses a quantitative research method, with a pre-experimental design and one group pretest and post-test technique. The population in this study were postpartum mothers aged 0-3 days at TPMB Yevi Yesevi, AMd.Keb. This study used a non-probability sampling procedure with a purposive sampling technique with a sample size of 30 respondents. Data analysis used univariate and bivariate analysis using the Wilcoxon Test. The results of the study on postpartum maternal breast milk production 0-3 days before the combination of oxytocin massage, lactation massage and acupressure mean 0.61, median 0.35, and standard deviation 0.6502. Postpartum maternal breast milk production 0-3 days after the combination of oxytocin massage, lactation massage and acupressure mean 2.6, median 2.60 and standard deviation 1.3564. The Wilcoxon test analysis obtained a Z value of -4.579 and an asymp sig. (2-tailed) value of 0.000 smaller than the alpha level of 5% (0.05) so Ha is accepted and H0 is rejected, so it can be concluded that there is an effect of the combination of oxytocin massage, lactation massage and acupressure on breast milk production in postpartum mothers 0-3 days.